Ceramics processing in microtechnology - Ritzhaupt-Kleissl, H.-J; Johander, Per (Whittles Pub., 2009)
This book provides an overview of the current status of processing of ceramic materials in micro technology. Emanating in part from scientific partners in the ceramics division of the European Network of Excellence, the book deals particularly with micro manufacturing and applications of ceramic materials. The book covers the spectrum of topics from design, through material development and synthesis, to microforming, thermal processing and metrology strategies, including characterization, quality control and the dependence of properties upon processing andmicrostructure. Processing technologies form a significant part of the book, and include replication techniques, tooling and mould fabrication and also special techniques such as embossing, electrophoretic deposition, high pressure injection moulding and prototyping. Subtractive and additive process technologies are dealt with, before the book concludes with sections on quality assurance, metrology, and test equipment for micro components.